Textbook oncologic outcomes and regionalization among patients undergoing hepatic resection for intrahepatic cholangiocarcinoma. Issue 1 (22nd September 2022) - Munir, Muhammad M.; Alaimo, Laura; Moazzam, Zorays; Endo, Yutaka; Lima, Henrique A.; Shaikh, Chanza; Ejaz, Aslam; Beane, Joal; Dillhoff, Mary; Cloyd, Jordan; Pawlik, Timothy M.
Abstract: Background and Objectives: Textbook oncologic outcome (TOO) and its association with regionalization of care for intrahepatic cholangiocarcinoma (ICC) have not been evaluated. Methods: We identified patients who underwent hepatic resection for ICC between 2004 and 2018 from the National Cancer Database. Facilities were categorized by annual hepatectomy volume for ICC. TOO was defined as no 90‐day mortality, margin‐negative resection, no prolonged hospitalization, no 30‐day readmission, receipt of appropriate adjuvant therapy, and adequate lymphadenectomy. Multivariable regression was used to evaluate the association between annual hepatectomy volume and TOO. Results: A total of 5359 patients underwent liver resection for ICC. TOO was achieved in 11.2% ( n  = 599) of patients. Inadequate lymphadenectomy was the largest impediment to achieving TOO. After adjusting for patient, pathologic, and facility characteristics, high volume facilities had 67% increased odds of achieving TOO (Ref.: low volume; high volume: odds ratio 1.67, 95% confidence interval: 1.24–2.25; p  < 0.001). Patients treated at high‐volume centers who achieved a TOO had better overall survival (OS) versus patients treated at low‐volume facilities (low volume vs. high volume; median OS, 47.3 vs. 71.1 months, p  < 0.05). Conclusions: A composite oncologic measure, TOO, provides a comprehensive insight into the performance of liver resection and regionalization of surgical care for ICC.